EXAMINING THE CONTENT ALIGNMENT BETWEEN LANGUAGE CURRICULUM AND A LANGUAGE TEST IN CHINA - Wallace, Matthew P; Ke, Haijiao (TEFLIN Journal, 2023)
This study examined the content alignment between an English as a foreign language skills curriculum and a provincial language test in China. When there is misalignment in the content between the standards of a curriculum and a test, conclusions about student abilities and teaching effectiveness can be questioned. To examine this, three categories of alignment were investigated using document analysis and expert judgment: categorical concurrence, range of knowledge correspondence, and balance of representation. Eight reviewers coded the curriculum and test items. Results showed that the curriculum aligned across the three criteria for the listening and reading skills. For the writing skills, the range of knowledge correspondence and balance of representation criteria were met, but categorical concurrence was not. The test did not include speaking items, so there was complete misalignment with that curriculum. The findings showed that the test partially aligned with the curriculum, suggesting that performance may not fully represent students’ ability to meet the curricular standards. We recommend that future tests should comprehensively cover all of the content in the curriculum and when doing so to ensure there is a sufficient number of items measuring each objective. This would improve how accurately interpretations of student performance can be made.